The culture of encounter as a strategy for continuing teacher training (Revista Internacional de Formação de Professores, 2025)
The article begins with the question: how do teaching proposals, emerging from the continuing education practices of the Franciscan Education Network, contribute to strengthening personal and professional development, fostering advances in the Network's educational proposal? The qualitative methodology used Franciscan hermeneutics for analysis and presents an excerpt from a doctoral dissertation, whose research was conducted in discussion groups with elementary school teachers from the Franciscan Education Network. One of the dissertation's findings points to the culture of encounter as a path toward continuing education. Although aware of the value of training through media, face-to-face encounters are considered a vital experience and give meaning to teacher education because, in the presence of others, self-construction becomes possible. Living in a predominantly virtual world, the teachers revealed that the main human longing remains the gaze, the embrace, the presence, the word, and the sharing of life.
Keywords: Training continues teaching. Meeting culture. Share. Teaching constitution.